THE INFLUENCE OF DEBATE METHOD TO STUDENTS CRITICAL THINKING IN EFL SETTING: IN SENIOR HIGH SCHOOL - Mutiara Haspari Lova; Setia Muljanto; Ateng Kurnia (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This study aims to analyze the impact of the debate method on the development of critical thinking and speaking skills of first-grade students at an Islamic High School. The research instruments include interviews and observations, with participants divided into two groups, each consisting of three students. Debate is used as a method to train critical thinking and speaking skills, which is believed to foster leadership qualities through students' roles in teams, while transforming students from passive recipients of information into active participants who take responsibility for their learning. Data were collected through interviews, where students were asked questions related to specific topics, as well as observations that monitored students' engagement during the wrong learning process, with these interviews serving as the foundation of qualitative research to explore participants' in-depth understanding. By combining interviews and observations, this study aims to describe the effectiveness of the debate method in the context of active learning. Data analysis was carried out using a structured qualitative framework consisting of three steps: data condensation, data display, and conclusion drawing/verification. Data condensation helps summarize and filter essential information, while data display visualizes findings to facilitate analysis. The final step, conclusion drawing and verification, generates an in-depth understanding of the impact of the debate method on students' skills. The findings of this study are expected to make a significant contribution to the development of active learning methods, particularly in enhancing students' critical thinking and speaking skills. With a structured approach, this study highlights the importance of the debate method in creating more interactive and meaningful learning experiences for students.